Implementation programme for the Common External Tariff and associate supporting measures (CCS GeorgetownGY, 1993)
The main decision adapted at the Conference of Heads of Government in October 1992, called for the establishment of a rate structure in the CET of 5 (0-5 LDC's) to 20 percent by January 1998 by way of a phased reduction of the current rate structure of the CET. This paper looks at the structure and operation of the CET; duty exemptions; implementation programme for CET and institutional arrangement for implementation of supporting policy measures.
DC